The effects of income fluctuations on rural health and nutrition - Kosec, Katrina; Song, Jie (International Food Policy Research Institute, 2019)
Our working paper, “The Effects of Income Fluctuations on Rural Health and Nutrition,” provides causal evidence on how the income fluctuations poor households confront across the globe influence health and nutrition outcomes across the life cycle. We use individual-level data from a 13-year, nationally-representative rotating panel survey of Kyrgyzstan to estimate the effects of fluctuations in the incomes of agriculture-dependent households on the heights and weights of young children (age 0–5) and on the incidence of overweight and obesity among children and adults. Our focus on departures of income from trend is distinct from analysis of the effects of long-term changes in income. It offers insight into how health responds to income fluctuations that are ubiquitous in developing countries rather than the impacts of global shifts in a country’s prosperity. We address the endogeneity of income to health and consumption using an instrumental variables approach; we instrument for income with predicted income, obtained using the household’s initial period share of income from six different revenue sources, agricultural production costs from two different sources (crop and livestock), and aggregate growth rates of each of these eight revenues and costs over time. We find that young children (age 0-5) exposed to reductions in income experienced reductions in height. At the same time, older children and adults saw decreases in BMI and—for adults—decreases in the incidence of overweight.